Effects of practical models of low-volume high-intensity interval training on glycemic control and insulin resistance in adults: a systematic review and meta-analysis of randomized controlled studies - Lu, Yining; Baker, Julien S.; Ying, Shanshan; Lu, Yichen (Frontiers in Endocrinology, 2025)
ObjectivesThe aim of this systematic review and meta-analysis was to investigate the effects of practical models of low-volume high-intensity interval training protocols (LV-HIIT) on glucose control and insulin resistance compared with moderate-intensity continuous training (MICT) protocols and no-exercise controls (CON).MethodsFour databases (PubMed, Web of Science, Scopus, and Cochrane Library) were searched for randomized controlled studies conducted using LV-HIIT interventions (HIIT/SIT protocols involving ≤ 15 min of intense training, within a session lasting ≤ 30 min; < 30 s all-out sprint for SIT additionally). The inclusion criteria required glucose and insulin resistance markers to be evaluated pre- and post-intervention among adults who were not trained athletes.ResultsAs a result, twenty studies were included, and meta-analyses were conducted using sixteen studies employing HIIT protocols. Compared with CON, LV-HIIT with reduced intensity and extended interval duration significantly improved fasting glucose (FPG) (mean difference (MD) in mg/dL=-16.63; 95% confidence interval (CI): -25.30 to -7.96; p<0.001) and HbA1c (MD=-0.70; 95% CI: -1.10 to -0.29; p<0.001). Greater improvements were found in participants who were overweight/obese or having type 2 diabetes (T2D). FPG decreased with every additional second of interval duration (β;=-0.10; 95% CI: -0.19 to -0.00; p=0.046). FPI (β;=-0.65; 95% CI: -1.27 to -0.02; p=0.042) and HOMA-IR (β;=-0.22; 95% CI: -0.36 to -0.09; p=0.001) decreased with every additional minute of interval duration per session. HOMA-IR also decreased with every additional minute of weekly interval duration (β;=-0.06; 95%CI: -0.08 to -0.04; p<0.001). Compared with MICT, LV-HIIT was more effective in improving insulin sensitivity (SMD=-0.40; 95%CI: -0.70 to -0.09; p=0.01), but there were no differences in FPG, FPI, HbA1c or HOMA-IR (p>0.05). The effect of LV-HIIT on FPI was larger compared with MICT among individuals who lost weight.ConclusionConclusively, a practical model of LV-HIIT with reduced intensity and extended interval was effective in improving glucose control and its effects were similar to MICT. Greater improvements were found in individuals with overweight/obesity or T2D in protocols with longer intervals or accumulated interval duration per session/week. More large-scale, randomized controlled studies with similar intervention protocols in a wide range of population are warranted to confirm these important results.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024516594.